2005
DOI: 10.1124/jpet.104.080648
|View full text |Cite
|
Sign up to set email alerts
|

Suramin Promotes Proliferation and Scattering of Renal Epithelial Cells

Abstract: Primary cultures of renal proximal tubules are known to recapitulate several early events in the process of renal regeneration following injury. In this study, we show that suramin, a polysulfonated naphthylurea, stimulates outgrowth, scattering, and proliferation of primary cultures of renal proximal tubule cells (RPTC). These responses were comparable to those produced by epidermal growth factor (EGF). However, AG-1478 [4-(3Ј-chloroanilino)-6,7-dimethoxy-quinazoline], a specific inhibitor of the EGF receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
4
13
1
Order By: Relevance
“…This effect of suramin on TGF-␤ 1 was associated with decreased apoptosis 48 h after glycerol treatment and increased proximal tubular cellular proliferation. This finding is consistent with our previous data showing that TGF-␤ 1 induces apoptosis in renal proximal tubular cells and that suramin stimulates the proliferation of renal proximal tubular cells in primary cultures by activating the Src/Phosphoinositide 3-kinase/Protein kinase B pathway (Zhuang and Schnellmann, 2005).…”
Section: Untreated D 72 H After Glycerol E 72 H After Glycerol + Susupporting
confidence: 83%
See 1 more Smart Citation
“…This effect of suramin on TGF-␤ 1 was associated with decreased apoptosis 48 h after glycerol treatment and increased proximal tubular cellular proliferation. This finding is consistent with our previous data showing that TGF-␤ 1 induces apoptosis in renal proximal tubular cells and that suramin stimulates the proliferation of renal proximal tubular cells in primary cultures by activating the Src/Phosphoinositide 3-kinase/Protein kinase B pathway (Zhuang and Schnellmann, 2005).…”
Section: Untreated D 72 H After Glycerol E 72 H After Glycerol + Susupporting
confidence: 83%
“…Recently, it was reported that the delayed administration of suramin, a polysulfonated naphthylurea used in humans to treat trypanosomiasis, accelerates recovery from renal dysfunction induced by ischemia/reperfusion (I/R) injury, renal fibrosis, and obstructive nephropathies in mice (Zhuang and Schnellmann, 2005;Zhuang et al, 2009;Liu et al, 2011a,b). The mechanisms by which suramin accelerates recovery from renal dysfunction in these models remain incompletely understood but may be associated with the inhibition of apoptosis, suppression of inflammatory cytokine production, and promotion of epithelial cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of suramin to block G protein-dependent signaling pathways has led to many studies documenting its anticancer effects. However, recent evidence suggests that suramin, in certain cell types such as Chinese hamster ovary cells and renal epithelial cells, may actually activate signaling pathways related to cell proliferation (Nakata, 2004;Zhuang and Schnellmann, 2005). In the present study, treatment of cells with suramin did not alter surface expression of AT 1A Rs, AngII-induced AT 1A R trafficking, p42/44 ERK activation, or COX-2 expression.…”
Section: Discussionmentioning
confidence: 42%
“…Surprisingly, suramin, which causes intracellular vesicular swelling and decreases intralysosomal proteolysis (7,8,26,27,29), slightly increased PCV2 infection of epithelial cells. Another suramin activity may be responsible for the enhanced PCV2 infection, such as the activation of DNA synthesis (53,71), since PCV2 replication is cell cycle dependent and the stimulation of cellular proliferation by suramin may help PCV2 to replicate.…”
Section: Discussionmentioning
confidence: 99%